Changes in Testicular Interstitial Connective Tissue of Hamsters (Mesocricetus auratus) During Ageing and After Exposure to Short Photoperiod. Issue 1 (25th November 2015) - Beltrán‐Frutos, E; Seco‐Rovira, V; Ferrer, C; Martínez‐Hernández, J; Madrid, JF; Sáez, FJ; Canteras, M; Pastor, LM
Contents: The testicular interstitium of Syrian hamster ( Mesocricetus auratus) was studied during ageing and in testicular regression after exposure to a short photoperiod, in relation to the interstitial cells and their connective tissue. This tissue was assessed histochemically using Masson's trichrome technique and the expression of Heat Shock Protein 47 (HSP‐47) and collagen IV ( α 5) was assessed in Leydig cells. Finally, an ultrastructural analysis of some cells of the testicular interstitium was made. Leydig cells were positive for HSP‐47 and collagen IV ( α 5). Ageing did not change the parameters studied while the short photoperiod altered the synthetic activity of Leydig cells. The positivity index of these cells for HSP‐47 was significantly higher in the regressed testis, but was lower for collagen IV ( α 5). During ageing no change were observed. Ultrastructural Leydig cells showed a discontinuous basal lamina that did not change during ageing. The basal lamina was not identified in Leydig cells regressed by exposure to a short photoperiod. In conclusion; the intertubular connective tissue suffers little change with age. By contrast, in the testis regressed after exposure to a short photoperiod the studied parameters related to the intertubular connective tissue were altered. These changes are probably related with the low synthetic activity of regressed Leydig cell.